ANALYZING THE IMPLEMENTATION OF DIFFERENTIATED LEARNING IN TEACHING WRITING SKILL: A CASE STUDY ON STRATEGY AND CHALLENGES - Riski Rosnanda; Nur Asmawati; Fatima (JURNAL PENDIDIKAN GLASSER, 2025)
Differentiated Learning has emerged as an educational strategy designed to accommodate the diverse characteristics, interests, readiness, and learning styles of students. This study aimed to analyze the implementation of differentiated learning and the challenges faced by English teachers in teaching writing skills. A qualitative case study design was employed, with data collected through classroom observations, semi-structured interviews, and documentation analysis. The research was conducted at SMPN 1 Palu, involving one English teacher and 31 eighth-grade students, with in-depth interviews conducted with three selected students and the teacher. The findings revealed that the teacher applied differentiation in four areas: content, process, product, and learning environment. Students were given varied materials tailored to their readiness levels, engaged in flexible group activities, and allowed to demonstrate understanding through multiple formats. These practices supported students' active participation, increased motivation, and fostered creativity in the writing process. Moreover, the teacher created a supportive and adaptive classroom environment that encouraged collaboration and comfort. However, the study also highlighted challenges, such as limited resources, difficulties addressing students with special needs, and the complexity of planning differentiated tasks. Despite these barriers, differentiated learning significantly enhanced the quality of English writing class in alignment with the Merdeka Belajar curriculum